Pendampingan Digitalisasi Posyandu Desa Ketapang melalui Aplikasi Google Maps dan Google Workspace - Rahma Dewi Anggreini; Diah Nur Novitasari; M. Zuhruf Firdaus; Rifky Ananta K; Izzatul Ulya; Fahruddin Ali Sabri (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
This community engagement focuses on assisting through the Google Workspace and Google Maps applications in the Ketapang village posyandu. The subjects involved were 23 cadres of the Ketapang village posyandu. The service aims to provide assistance to posyandu cadres in utilizing Google Workspace and Google Maps as a medium to improve the optimization of village development in better and more efficient. The methods used include seminars, question and answer sessions, and assistance in applying Google Workspace and Google maps. The results of this activity showed a significant increase in digital literacy of Ketapang village posyandu cadres. The resulting impact includes increased optimization of Google accounts. This service demonstrates the importance of utilizing digital technology in supporting the development of health administration and services in Ketapang village. Keywords: Posyandu;Digital Literacy;Google Workspace;Google Maps;Ketapang